2011
DOI: 10.2460/ajvr.72.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding a high-protein diet following an 18-hour period of feed withholding on mammalian target of rapamycin-dependent signaling in skeletal muscle of mature horses

Abstract: In mature horses, feeding resulted in increased mammalian target of rapamycin signaling and the mechanism appeared to be independent of an increase in Akt phosphorylation at Ser⁴⁷³. Results indicate that adult horses may be able to increase rates of muscle protein synthesis in response to feeding and that dietary amino acids appear to be the main mediators of this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 42 publications
2
40
4
Order By: Relevance
“…Generally, studies 20,3638 in which a beneficial effect on muscle mTOR signaling activation was identified for dietary supplementation with leucine or branched chain amino acids involved a rate of supplementation that resulted in at least a doubling of plasma leucine concentration. Although plasma amino acid concentrations were not measured in our study, previous studies 4,5 involving similar horse feeding protocols showed that plasma branched chain amino acid concentrations were only 24% to 45% higher than preprandial concentrations 60 to 80 minutes after feeding. The muscle branched chain amino acid concentrations at the 8-cm biopsy depth were significantly greater than those at the other depths in the present study, but the 25% to 33% increase in their concentrations did not appear large enough to elicit an increase in the mTOR signaling response.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…Generally, studies 20,3638 in which a beneficial effect on muscle mTOR signaling activation was identified for dietary supplementation with leucine or branched chain amino acids involved a rate of supplementation that resulted in at least a doubling of plasma leucine concentration. Although plasma amino acid concentrations were not measured in our study, previous studies 4,5 involving similar horse feeding protocols showed that plasma branched chain amino acid concentrations were only 24% to 45% higher than preprandial concentrations 60 to 80 minutes after feeding. The muscle branched chain amino acid concentrations at the 8-cm biopsy depth were significantly greater than those at the other depths in the present study, but the 25% to 33% increase in their concentrations did not appear large enough to elicit an increase in the mTOR signaling response.…”
Section: Discussioncontrasting
confidence: 59%
“…The amino acid composition of the high-protein pellet has been reported elsewhere. 5 A feeding protocol similar to the one used in the present study resulted in a 4-fold increase in plasma insulin concentration, an approximately 25% to 125% increase in plasma concentrations of indispensable (essential) amino acids, and an increase in the degree of upstream and downstream mTOR signaling in the gluteus medius muscle in the postprandial versus postabsorptive state. 4,5 …”
Section: Methodsmentioning
confidence: 65%
See 3 more Smart Citations